Digitally-supported language exchanges in primary school: The AlpConnectar project - Botturi, Luca; Kapler, Daniela; Negrini, Lucio (Studies in Second Language Learning and Teaching, 2018)
This article presents the design, implementation and outcomes of AlpConnectar, a Swiss project that exploits technologies for digitally-supported language exchange (LE) in primary schools. Launched in 2013, the project involves three Swiss cantons where different languages are spoken (namely German, French and Italian) and respectively taught as foreign languages since the third grade of primary school. In the first section of the paper the linguistic composition of Switzerland is briefly presented and the current methodologies and approaches in foreign language teaching in the country are introduced. After a literature review of online LE practices, the AlpConnectar project is presented, along with a LE example to illustrate how it works. The final sections present the results of the project, based on data collected from both pupils and teachers. The results seem to suggest that while digital technologies offer significant benefits for LEs, they are no silver bullet, and their impact depends on a number of contextual variables.